2008
DOI: 10.1016/j.ejcts.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Serious complications following endovascular thoracic aortic stent-graft repair for type B dissection

Abstract: Endovascular stent-graft repair of the thoracic aorta is an alternative to surgical repair, however not without significant morbidity and mortality. Potentially lethal complications, acute or delayed, may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 23 publications
(67 reference statements)
0
86
3
5
Order By: Relevance
“…The third patient had a preexisting retrograde propagation of the dissection into the arch and a natural fenestration at the origin of the left common carotid artery, which did not resolve with embolization of the LSCA and adjacent aortic false lumen. This patient and 3 others underwent elective surgical repair at 8,8,6, and 3 months after stent-graft treatment, all of which were successful in removing endoleak-related dilatation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The third patient had a preexisting retrograde propagation of the dissection into the arch and a natural fenestration at the origin of the left common carotid artery, which did not resolve with embolization of the LSCA and adjacent aortic false lumen. This patient and 3 others underwent elective surgical repair at 8,8,6, and 3 months after stent-graft treatment, all of which were successful in removing endoleak-related dilatation.…”
Section: Resultsmentioning
confidence: 98%
“…1,2 Goals of stent-graft placement are to reestablish arterial flow to ischemic beds and to abolish pulsatile antegrade perfusion of the false lumen, which should reduce subsequent false lumen enlargement and rupture. [3][4][5][6][7][8] Continued pressurization and perfusion of the false lumen due to endoleak, however, is frequently seen after stent-graft repair of aortic dissection. 9,10 Compared with endoleaks encountered after thoracic endovascular aneurysm repair, endoleak physiology in aortic dissection is complex and incompletely understood.…”
mentioning
confidence: 99%
“…Suitable patients should be hemodynamically stable and the ascending aortic FL thrombosed while the ascending aorta is preferably not severely dilated (ie, <5.5 cm). Recently, there has been a plethora of studies on retro-A AD occurring secondarily to thoracic endovascular aortic repair, [8][9][10] but the literature on spontaneous acute retro-A AD, which is a distinct entity, is limited. Previous studies were mostly conducted on small patient cohorts or mentioned through case reports.…”
Section: Discussionmentioning
confidence: 99%
“…12 Fourth, retrograde Stanford A dissection is the serious complication of TEVAR for AAD(B). 13 Fifth, although long-term results have not yet been established, Khoynezhad et al reported 1-and 5-year survival rates of 82% and 78%, respectively. 14 Vorhoye et al reported 1-and 5-year survival rates of 73% for each and that the false lumen was completely thrombosed in 25% patients and partially thrombosed in 38%.…”
Section: Discussionmentioning
confidence: 96%
“…15 A patent false lumen is a risk factor for long-term survival; therefore, a thrombosed false lumen suggests good long-term results. However, a catastrophic complication, retrograde Stanford A dissection, could occur even days, weeks, or months following TEVAR 13 . Therefore careful follow-up is mandatory.…”
Section: Discussionmentioning
confidence: 99%